SDM Efektif Menuju Pesantren Bermutu, Studi Penelitian Pondok Pesantren Ibnu Kholdun Al Hasyimi - Goffar, Abdul; Fawait, Agus; Nuryawati, Hemi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study aims to reveal the applied pattern of the formation of effective HR performance. This study took place at the Ibnu Kholdun Al Hasyimi Widoropayung Besuki Islamic Boarding School. This data collection used a qualitative case study approach. Data acquisition through observation and interviews with the regional head, one of the administrators, and one of the students. The data analysis procedure is data collection, data presentation, data reduction, and drawing conclusions. The results of the study indicate that effective HR performance towards a quality Islamic boarding school includes: Administrators have potential, have high desires, and get support from leaders. The results of the study indicate the success and implementation of effective human resource performance towards a quality Islamic boarding school. This pattern is a good contribution to the sustainability of Islamic Boarding Schools towards the tight competition of education in the future global era